An Analysis of the Indonesian Language Textbook 'Aku yang Unik' for Grade 5: An Evaluation Based on BSNP Feasibility Criteria - Musfidah; Purwati, Panca Dewi; Aribah, Talitha Hasna; Ilmi, Mahayu Ulayya; Labibah, Saila; Hidayat, Getasiandika Mulya (Lembaga KITA, 2025)
In primary education, textbooks serve as a cornerstone for the learning process, playing a pivotal role in achieving educational goals. A high-quality textbook not only aligns with the curriculum but also uses precise language, features appealing visuals, and inspires students to engage actively in learning. For this reason, it is essential to evaluate the suitability of textbooks before they are adopted in classroom instruction. The Indonesian language textbook “Bergerak Bersama” for fifth-grade students is among those implemented under the Merdeka Curriculum, making a feasibility review—particularly of Chapter I, “Aku yang Unik”—crucial to ensure its positive impact on both teaching and learning outcomes. This study examines the appropriateness of content quality, language use, presentation style, and graphic design within Chapter I of the aforementioned textbook. The central question addressed is the extent to which the book meets the standards across these four dimensions. A qualitative descriptive approach was employed, utilizing document analysis as the primary method. Data were collected through direct assessment of Chapter I, following the BSNP textbook eligibility instrument, with each aspect evaluated based on established BSNP indicators. Findings reveal that, in terms of content, the material corresponds well with the latest curriculum objectives and remains relevant, especially in introducing adjectives, affixes, synonyms, antonyms, and compound sentences. Linguistically, the textbook adheres to the Indonesian spelling guidelines (PUEBI), and the language is clear and accessible to students. Regarding presentation, the textbook is considered engaging and motivating, further supported by comprehensive practice questions at the end of each chapter. Visually, choices in typography, formatting, and illustrations meet accepted standards and enhance student comprehension. The analysis indicates that Chapter I of “Bergerak Bersama” fulfills the BSNP’s criteria for use as a teaching resource in elementary schools. The four dimensions—content, language, presentation, and visual design—are all adequately addressed, supporting an effective and enjoyable learning experience. Consequently, this textbook stands as a relevant and reliable primary learning resource aligned with the curriculum and the needs of students